Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jop.12328
|View full text |Cite
|
Sign up to set email alerts
|

The role of patch testing in the management of oral lichenoid reactions

Abstract: Skin patch testing is a valuable tool to confirm clinically suspected oral lichenoid reactions. Pathology diagnoses of oral lichenoid reactions did not correlate with patch test results. Prospective studies are needed to ascertain that a clinically suspected oral lichenoid reaction with a positive patch test result may resolve after the replacement of amalgam fillings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…OLRs also occur in betel-quid chewers at the site of placement of betel quid (Figure 9). The diagnosis of OLPs/OLLs/OLRs is mostly based on the combined findings from history; clinical examination; a skin patch test, when indicated 20 ; and microscopy. In cases of OLLs/OLRs suspected to be drug induced, the history of any correlation between the start of medication intake and first symptoms may also be informative, even though reactions can occur several weeks or months after the prescription.…”
Section: Oral Lichenoid Lesionsmentioning
confidence: 99%
“…OLRs also occur in betel-quid chewers at the site of placement of betel quid (Figure 9). The diagnosis of OLPs/OLLs/OLRs is mostly based on the combined findings from history; clinical examination; a skin patch test, when indicated 20 ; and microscopy. In cases of OLLs/OLRs suspected to be drug induced, the history of any correlation between the start of medication intake and first symptoms may also be informative, even though reactions can occur several weeks or months after the prescription.…”
Section: Oral Lichenoid Lesionsmentioning
confidence: 99%
“…In terms of general dental materials, positive patch testing results in OLP patients vary from 60 to 80 % [3,14]. Mercury is highly allergenic and often present in dental amalgams.…”
Section: Oral Lichen Planus and Oral Lichenoid Lesionsmentioning
confidence: 97%
“…There is a body of research on the clinical results of OLP patients following dental amalgam removal and its association with patch testing [14,17,[20][21][22][23][24][25]. A systematic review of 14 cohort and five case-controlled trials of patients with OLP demonstrated that after dental amalgam replacement, between 35 and 100 % of patients had complete disease resolution.…”
Section: Oral Lichen Planus and Oral Lichenoid Lesionsmentioning
confidence: 98%
“…They are commonly unilateral and erythematous and histopathological examination shows more diffuse lymphocytic infiltrate with eosinophils and plasma cells and with more colloid bodies than in classic OLP; on the other hand, to the best of our knowledge there is no study published which has demonstrated accurate histopathological features to distinguish between OLP and OLCR lesions (5,9). Skin patch testing against dental restorative materials helps to distinguish patients with OLCR, and after removal of these causative materials, the majority of lesions may resolve within several months (8,10).…”
Section: Introductionmentioning
confidence: 99%